STUDI SIKUEN STRATIGRAFI ENDAPAN BERUMUR OLIGOSEN ATAS – MIOSEN BAWAH (P22 – N6) CEKUNGAN JAWA TIMUR UTARA DI DAERAH TUBAN JAWA TIMUR - Pontjomojono Kundanurdoro (Jurnal Ilmiah MTG, 2009)
Sequence stratigraphic analysis can application at all deposition environment and can be determined base on outcrop data and well data. This Research trying to apply overflows and foraminifera uniform at deep-sea deposition of old age Upper Oligocene-Lower Miocene in the North East Java basin consisting of 3 formations. This Research analyzing 91 sample from 4 MS and can compiled become 6 sequence.Maximum Flooding Surface (MFS) can determined base on total overflows top foraminifera, sequence boundary (SB) in the existence of change of paleobathymetri, lithology characteristic, and degradation of total overflows among two MFS.Sequence 1 is limited by SB 1 in the research area, MFS 1 in the show total what overflows top of foraminifera at K.05 (1085/100 gr), structured by claystone insert bioclastic limestone, sequence 2 limited by SB2 in the show existence of superficiality outer neritic to middle neritic among MFS1 and MFS2, MFS2 in the show total overflows top of foraminifera at Ps.40 (499/100gr), compiled by claystone insert bioclastic limestone. Sequence 3 limited by SB3 in the show existence of superficiality from lower bathyal to outer neritic among MFS2 and MFS3, MFS3 in the show total overflows top of foraminifera at G.06 (2858/10gr), compiled by claystone insert fragmental limestone, sandstone and containing “clay ironstone nodul”. Sequence 4 limited by SB34 in the show existence of superficiality from upper bathyal to outer neritic among MFS3 and MFS4, MFS4 in the show total overflows top of foraminifera at G.14F (4987/100gr), compiled by claystone insert fragmental limestone and interlaminated bioclastic limestone, chalk limestone. Sequence 5 limited by SB5 in the show existence of superficiality upper bathyal to middle neritic among MFS4 and MFS5, MFS5 in the show culminate total overflows of foraminifera at Sd.23. (302/100gr), compiled by interlaminated bioclastic limestone and chalk limestone, claystone, and marl. Sequence limited by SB6 in the show existence of superficiality outer neritic to middle neritic among MFS5 and MFS6, MFS6 in the show maximum overflows foraminifera at Sd.32. (274/100 gr), compiled by claystone insert shalestone and clay ironstone nodul.